The role of glioma stem cells in chemotherapy resistance and glioblastoma multiforme recurrence. (July 2015) - Auffinger, Brenda; Spencer, Drew; Pytel, Peter; Ahmed, Atique U; Lesniak, Maciej S
<x xml:space="preserve">Abstract</x> Glioma stem cells (GSCs) constitute a slow-dividing, small population within a heterogeneous glioblastoma. They are able to self-renew, recapitulate a whole tumor, and differentiate into other specific glioblastoma multiforme (GBM) subpopulations. Therefore, they have been held responsible for malignant relapse after primary standard therapy and the poor prognosis of recurrent GBM. The failure of current therapies to eliminate specific GSC subpopulations has been considered a major factor contributing to the inevitable recurrence in GBM patients after treatment. Here, we discuss the molecular mechanisms of chemoresistance of GSCs and the reasons why complete eradication of GSCs is so difficult to achieve. We will also describe the targeted therapies currently available for GSCs and possible mechanisms to overcome such chemoresistance and avoid therapeutic relapse.